2009
DOI: 10.1111/j.1440-0960.2008.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of refractory pyoderma gangrenosum with intravenous immunoglobulin

Abstract: We report a patient with pyoderma gangrenosum successfully treated with intravenous immunoglobulin. He had previously been treated for 4 years with high-dose corticosteroids and had developed insulin-dependent diabetes mellitus. Multiple corticosteroid-sparing agents had failed or were contraindicated. He developed no adverse effects from intravenous immunoglobulin, which allowed reduction of his prednisone to 3 mg/day, and his ulcer has completely healed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Our literature search yielded 26 articles, which describe 43 cases of PG treated with IVIG (see Fig. and Table S1; see Supporting Information) . The retrospective review identified six patients with PG treated with IVIG at our institutions.…”
Section: Resultsmentioning
confidence: 99%
“…Our literature search yielded 26 articles, which describe 43 cases of PG treated with IVIG (see Fig. and Table S1; see Supporting Information) . The retrospective review identified six patients with PG treated with IVIG at our institutions.…”
Section: Resultsmentioning
confidence: 99%
“…First report of successful therapy for leg ulcer with IVIG was published in 1998 [28]. Since IVIG was widely used for therapy of refractory leg ulcers due to pyoderma gangrenosum [28,29], RA [30], livedoid vasculitis [31], periarteritis nodosa [32,33], chronic leucocytoclastic vasculitis [34]. We used schedule 0.4 g/kg/day for 5 days every month [27], which proved to be successful.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated include those with and without other underlying disorders, like inflammatory bowel disease RA, and myelodysplastic syndromes. [251252253254255]…”
Section: Intravenous Immunoglobulin (Ivig)mentioning
confidence: 99%